Patient-physician discordance in assessment of adherence to inhaled controller medication - Jácome, Cristina (2019)
CJ is a post-doc fellow (SFRH/BPD/115169/2016) funded by Fundação para a Ciência e Tecnologia (FCT), reimbursed by Fundo Social Europeu and by national funds of MCTES. This work was funded by ERDF (European Regional Development Fund) through the operations: POCI-01-0145-FEDER-029130 ('mINSPIRERS—mHealth to measure and improve adherence to medication in chronic obstructive respiratory diseases—generalisation and evaluation of gamification, peer support and advanced image processing technologies') cofunded by the COMPETE2020 (Programa Operacional Competitividade e Internacionalização), Portugal 2020 and by Portuguese Funds through FCT (Fundação para a Ciência e a Tecnologia).